Training in Accessible Filmmaking - Romero-Fresco, Pablo (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Accessible filmmaking (AFM), that is, the integration of audiovisual translation (AVT) and media accessibility (MA) into the filmmaking process through collaboration between filmmakers and translators/MA experts, has developed significantly over the past few years. It has been endorsed by filmmakers such as Ken Loach and institutions such as the British Film Institute (BFI), which has decided to embrace it as a key element in the production of films and the training of future filmmakers. However, current training in AFM is at best anecdotal. This article aims to address this gap by proposing two different courses on AFM. By way of introduction, section 2 sets the background with an analysis of the reasons behind the division between film and AVT/MA. Special attention is paid to the invisibility of AVT/MA in Film Studies and to the new AVT/MA-aware notion of film that underpins the current proposal for AFM training. Sections 3 and 4 provide an overview of the training currently available in AVT/MA and film(-making). Finally, section 5 offers an account of the first pioneering attempts to provide AFM training and, most importantly, a proposed outline for two different courses designed to equip accessible filmmakers and translators/MA experts with the required skills and competences to apply the AFM model.